THE ROLE OF SHARIA INVESTMENT GALLERY IN INCREASING STUDENT INTEREST IN INVESTING SHARIA STOCKS AT THE ISLAMIC UNIVERSITY OF INDONESIA - Lukluil Mukarromah (JURNAL BISNIS STRATEGI, 2022)
This study is a study that aims to determine the effectiveness of sharia investment galleries in increasing the interest of students who invest in sharia shares at the Indonesian Islamic University. This research is qualitative which describes the phenomena and actual conditions of the data objects studied, based on field findings and then analyzed and presented in the form of descriptive information. The results of this study indicate that the sharia investment gallery at the Islamic University of Indonesia is quite capable of attracting students to invest in sharia shares in the sharia investment gallery of the Islamic University of Indonesia. However, it needs to be re-optimized after Covid-19 by increasing literacy among students.